THE INFLUENCE OF MACROECONOMIC VARIABLES TOWARD JAKARTA COMPOSITE INDEX ON INDONESIA STOCK EXCHANGE - Rifqi Nur Wahyudi (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2017)
This study aimed to get empirical evidence macroeconomic variable : money supply, gross domestic product, inflation, BI Rate, exchange rate IDR/USD toward JCI. This research conducted by examine the data in the period January 2007 – December 2016. The research technique is using multiple linear regression analysis. The result showed that the Money Supply and GDP positive but not significant effect, inflation negative and not significant,BI Rate and exchange rate IDR / USD negative and significant effect on the Jakarta Composite Index. Keywords: Money Supply, Gross Domestic Product, Inflation, BI Rate, Exchange Rate IDR/USD, JCI